“A Modest Soldier in the Great Army of Communists”: VisualRepresentations of Women in Ceaușescu’s Romania - Teampău, Petruța (Contemporary Southeastern Europe, 2024)
My research investigates, using discourse analysis and visual semiotics, the norms andideological guidelines of Communist propaganda regarding gender identity and sex roles, asexpressed in the magazine Femeia, between 1965-1989. Femeia was, at the time, the officialmedia outlet of the National Council of Women, directly involved in educating andmobilising women. The discourse and visuals of Femeia reinforce the idea that, in fact,women were the collective character of women’s emancipation, as anonymity was crucial ina totalitarian regime that did not tolerate individualism but advocated abnegation, selfsacrificeand devotion.